AMOBILISASI PEKTINASE HASIL ISOLASI DARI Aspergillus niger MENGGUNAKAN MATRIKS KARAGENAN - Tanjung, Elvanila; Roosdiana, Anna; Mardiana, Diah (Jurnal Ilmu Kimia Universitas Brawijaya, 2013)
ABSTRACT Pectinase isolated from Aspergillus niger was immobilized by entrapping method in a matrix of carrageenan. The aim of this research was to determine the optimum concentration of carrageenan and enzyme. Carrageenan concentration varied (0.017; 0.033; 0.050; 0.067; 0.083) g/mL, while the concentration of enzyme  varied  (0.632; 1.263; 1.895; 2.526; 3.158) mg/mL. Protein content was determined by Biuret reagent  and enzyme activity was determined from the number of reduced sugar as a result of  hydrolyzed pectin per minute. The results showed that optimum concentration of carrageenan was 0.050 g/mL and the optimum enzyme concentration was 1.263 mg/mL with the amount of entrapping enzyme was 3.048 mg/g carrageenan and maximum activity of  348.5 units. Key words: activity, Aspergillus niger, carrageenan, pectinase.